The Great Dewey Hunt - Buzzeo, Toni.; Yoshikawa, Sachiko (Janesville, Wis. : UpstartBooks, 2009)
Twins Hugh and Louis Abernathy take the lead when their fourth grade class hosts Mr. Hester's second grade class for Mrs. Skorupski's Great Dewey Hunt.
Lesson plan: The great Dewey hunt : library lessons.
Keywords: School librarians -- Juvenile fiction; Elementary schools -- Juvenile fiction; Classification, Dewey decimal -- Study and teaching (Elementary); Classification, Dewey decimal -- Fiction; Librarians -- Fiction; Libraries -- Fiction; Schools -- Fiction